Hemifacial spasm: a 42 patients series analysis treated with microvascular decompression.: https://doi.org/10.59156/revista.v37i02.506 - Funes, Pedro Tomas; Villalonga, Juan; Baldoncini, Matías; Campero, Álvaro (Revista Argentina de Neurocirugía, 2023)
Background. Hemifacial spasm is a rare condition characterized by unilateral, paroxysmal, and involuntary contraction of the facial muscles innervated by the facial nerve, caused in most cases by a vascular conflict in the cisternal course of the nerve. Objectives. To present the results of a series of patients who underwent microvascular decompression by hemifacial spasm. Methods. From June 2005 to September 2022, 42 patients underwent surgery; age, gender, time of evolution, side of the condition, the performance of botulinum toxin, intraoperative findings, post-surgical results, and complications were evaluated. Surgical technique. The semi-sitting position and a retrosigmoid approach were used. In the cistern, arachnoid dissection of the flocculus was performed to allow reclining it from the bottom to up and expose the exit zone of the facial nerve. Teflon felt was interposed, and the use of fibrin glue was adjusted according to the case. Results. The average age was 49.6 years, with 61.9% women. The right side was affected in 20 cases. The vessel most frequently identified in surgery was the anterior inferior cerebellar artery (20 cases). The response was total in 37 cases, partial in 3 cases, and null in 2 cases. Transitory deficits occurred in 9 cases and permanent deficits in 2 cases. Conclusion. Most of the patients in our series obtained a total improvement in the spasm. Decompression should be considered the first line of treatment for primary hemifacial spasms.
Keywords: Microvascular decompression; Hemifacial spasm; Flocculus; Teflon felt